Cultures of learning in developing education systems: Government and NGO classrooms in India. (2019) - Kumar, Anshul
Highlights: Observed mainstream government teachers openly discriminate against less capable students. Observed NGO teachers behave inclusively towards all types of students. Government teachers in the study do not appear open to adopting the NGO culture of learning. Additional teacher training is recommended to work against existing biases. Abstract: School culture is known to be important for positive student outcomes. This study examines the unique situation in which two distinct cultures of learning—propagated by government and NGO teachers—coexist in the same learning environments in Delhi, India. Based on data from four government schools, observed government-teacher classrooms tended to exhibit discrimination against supposed non-learners, a focus on discipline and rote learning, and inefficient time use. Observed NGO-teacher classrooms featured inclusive, creative teaching styles and more efficient time use. Government teachers were not observed to adopt NGO-specific behaviors, while NGO teachers appeared to be limited by the government school environment.